Penilaian Organoleptik Sebagai Analisa Sensori pada Produk Masker Badan dari Buah Naga (Hylocereus Polyrhizus) - Pritasari, Octaverina (Journal of Beauty and Cosmetology (JBC), 2019)
Body masks are cosmetics that are used at the last stage in body care, which works to remove dead skin cells. Body masks consist of basic ingredients, active ingredients and other supplementary ingredients. In this research, a mixture of dragon fruit skin flour and cow's milk kefir flour is used as an ingredient for making body masks. Dragon's skin flour contains a variety of vitamins and the hormone melatonin which functions as an antioxidant and a better aging process for youth. This is an experimental research. Data on organoleptic properties of body mask products were collected using the observation method of 30 panelists. The data analysis technique used is the single ANOVA and Duncan advanced test. The results showed that 1) the proportion of dragon fruit peel flour and kefir flour (30%: 70%) was the best face mask product with the criteria of white color, smooth texture, flavored kefir, and sticky and tight. 2) There is a difference between the composition of dragon fruit skin flour and kefir in an organoleptic body mask. This is discussed by the results of color with P = 0.00 (<0.05) and F-count 97.474, Texture P = 0.00 (<0.05) and F-count 10.906, aroma P = 0.00 (<0.05) and F-count 105.034, adhesion to P = 0.00 (<0.05) and F-count 94.179. The results of the analysis concluded that the best body masks on the proportion of dragon fruit skin flour and kefir flour is 30 percent: 70 percent.Keywords: sensory; bodymask; dragon fruit; kefir